2021
DOI: 10.1037/met0000377
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of the missing not at random missing data mechanism.

Abstract: Missing values that are missing not at random (MNAR) can result from a variety of missingness processes. However, two fundamental subtypes of MNAR values can be obtained from the definition of the MNAR mechanism itself. The distinction between them deserves consideration because they have characteristic differences in how they distort relationships in the data. This has implications for the validity of statistical results and generalizability of methodological findings that are based on data (empirical or gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Another interesting development related to Rubin's framework is the use of graphical models-directed acyclic graphs and missingness graphs (m-graphs)-to represent and understand missing data mechanisms. To illustrate, the m-graphs in Figure 1 depict the focused and diffuse missing not at random processes described by (Gomer & Yuan, 2021). Schafer and Graham (2002) used a similar diagram to represent Rubin's mechanisms, and others have since developed the framework as tool for understanding and clarifying the conditions under which valid estimates are possible (R. M. Daniel et al, 2012;Mohan et al, 2013;Mohan & Pearl, 2021;Moreno-Betancur et al, 2018;Thoemmes & Mohan, 2015;Thoemmes & Rose, 2014).…”
Section: Missing Data Mechanismsmentioning
confidence: 99%
“…Another interesting development related to Rubin's framework is the use of graphical models-directed acyclic graphs and missingness graphs (m-graphs)-to represent and understand missing data mechanisms. To illustrate, the m-graphs in Figure 1 depict the focused and diffuse missing not at random processes described by (Gomer & Yuan, 2021). Schafer and Graham (2002) used a similar diagram to represent Rubin's mechanisms, and others have since developed the framework as tool for understanding and clarifying the conditions under which valid estimates are possible (R. M. Daniel et al, 2012;Mohan et al, 2013;Mohan & Pearl, 2021;Moreno-Betancur et al, 2018;Thoemmes & Mohan, 2015;Thoemmes & Rose, 2014).…”
Section: Missing Data Mechanismsmentioning
confidence: 99%
“…Other approaches should not go unmentioned. For instance, research has suggested distinguishing different subtypes of the MNAR missing data mechanism [57]. Sensitivity analyses may also be implemented using multiple imputation [58][59][60] or Bayesian statistics [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…In general, both pairwise and listwise deletion result in lower statistical power, under any missing data mechanism (Enders & Bandalos, 2001). Moreover, if the missing data come from MAR or MNAR, then a model’s parameter estimates may be biased (Gomer & Yuan, in press).…”
Section: Missing Datamentioning
confidence: 99%